Genealogy of Conflict among Bone and Luwu Students in Makassar City - Sopian - Tamrin (LPPM Universitas PGRI Sumatera Barat, 2022)
The phenomenon of conflict among students that have occurred recently raises several questions. Is this conflict in accordance with the specific factors of each case or has certain socio-cultural roots. If that so, why do conflicts occur more often against certain areas. Why does the conflict always recur even though reconciliation has been carried out every time the conflict occurs. This research has some purposes: firstly, finding out the social and cultural roots of conflict among Bone and Luwu students. Secondly; finding how to handle regional conflicts among students. This research is descriptive qualitative by using knowledge geneaology approach from Michel Foucault. Research data obtained through observation, in-depth interviews and documentations. The results showed that a) the phenomenon of conflict among Bone and Luwu students had socio-cultural roots that were produced in the form of internal knowledge from generation to generation. The birth of the local organization of commissariat on campus marked a period of significant discontinuity producing inter-regional conflict. In addition, the functional of regional organizations as regeneration spaces that perpetuate fanaticism; b) regional organizations need to encourage an inclusive regeneration curriculum. In addition, it is very important to carry out social and spatial engineering that allows inclusive activities to live on campus by strengthening student institutions.